A PORTRAYAL OF MAIN CHARACTER’S INTERPERSONAL BEHAVIOR IN NINA LACOUR’S WE ARE OKAY - Veti Saputri; Erika Citra Sari Hartanto (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this study was to find out interpersonal behavior portrayed by the main character in We Are Okay by Nina LaCour. The analysis of this novel uses the theory of psychoanalysis that focuses on interpersonal behavior by William Schutz. It also explains the impact of interpersonal behavior in Marin and Mabel as the main character. The research of this study used qualitative research methods. The source of data of this study is the novel We Are Okay. The data of this study are the character’s utterances and author’s narration. Analysis of the data used five processes by Yin (2016); Compiling, Disassembling, Reassembling (and Arraying), Interpreting, and Concluding. The results showed the findings of inclusion, control, and affection in Marin and Mabel’s friendship. Then, the impact of interpersonal behavior are; Marin included Expressed behavior which became an open and loyal person, while Mabel included Wanted behavior which became a pleasant person and made herself available to others.